Peningkatan Ketahanan Pakan Ternak Dan Kebersihan Lingkungan Melalui Introduksi Budidaya Maggot di Padukuhan Jambu - Azrial, Fahmi; Pramudita, Ananda; Widyanna, Widyanna; Fauzi, Ibnu Nur; Setyaning, Agustin; Damayanti, Arsita Fitria; Iftinan, Kikan Hasna; Rahman, Muhammad Akmal; Azizi, Muhammad Arif Rakhman; Putri, Tiara Qur’rota Akyun Suroto; Yusuf, Muhammad; Isra, Nur (Universitas Methodist Indonesia, 2025)
Padukuhan Jambu in Sleman Regency, Special Region of Yogyakarta, faces two major challenges: high livestock feed costs and inadequate organic waste management. These issues significantly impact the economy of small-scale farmers and the local environment. Maggot cultivation (Black Soldier Fly larvae) was introduced as an integrated solution, offering a highly nutritious alternative livestock feed while providing an effective method for decomposing organic waste. This activity aims to enhance livestock feed security and environmental cleanliness, with expected benefits including reduced feed costs, increased community income, reduction in organic waste volume, and improved awareness of sustainable waste management. The project employed an Asset-Based Community Development (ABCD) approach, encompassing asset mapping, appreciative inquiry, and capacity building. The implementation of maggot cultivation in Padukuhan Jambu showed positive results, with active participation of about 60 residents in the training program. Economic impacts were evident in the reduction of livestock feed costs and potential new income from maggot sales. Environmentally, there was a decrease in organic waste volume and improved sanitation. Social impacts included enhanced community cohesion and empowerment through the formation of maggot farming groups. This program successfully integrated solutions for livestock feed security and organic waste management while improving community welfare and self-reliance.